2009
DOI: 10.1111/j.1467-7687.2009.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between manual preferences for object manipulation and pointing gestures in infants and toddlers

Abstract: The aim of this study was to measure the pattern of hand preferences for pointing gestures as a function of object-manipulation handedness in 123 infants and toddlers (10-40 months). The results showed that not only right-handers but also left-handers and ambidextrous participants tended to use their right hand for pointing. There was a significant correlation between manual preferences and pointing lateralization. Further analyses showed that the correlation between these two indexes was at its strongest duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
87
6
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 41 publications
9
87
6
5
Order By: Relevance
“…First, a right-hand preference was observed for both bimanual manipulation and pointing gestures, confirming the results reported in several prior studies (e.g., Bates et al, 1986;Cochet & Vauclair, 2010a, 2010bFagard & Marks, 2000;Vauclair & Imbault, 2009;Young et al, 1985).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…First, a right-hand preference was observed for both bimanual manipulation and pointing gestures, confirming the results reported in several prior studies (e.g., Bates et al, 1986;Cochet & Vauclair, 2010a, 2010bFagard & Marks, 2000;Vauclair & Imbault, 2009;Young et al, 1985).…”
Section: Discussionsupporting
confidence: 90%
“…A right-sided asymmetry especially for pointing gestures has been reported in several studies (Bates et al, 1986;Blake, O'Rourke, & Borzellino, 1994;Vauclair & Imbault, 2009;Young, Lock, & Service, 1985). Moreover, Esseily et al (2011) showed that right-handed infants for pointing understood and produced more words than non-right-handed infants, and Vauclair and Cochet (2010) observed a U-shaped relationship in toddlers between 12 and 30 months of age between the degree of hand preference for pointing and the developmental quotient for language.…”
Section: Handedness For Pointing and Language Developmentmentioning
confidence: 56%
See 3 more Smart Citations